In vitro studies on survival of encapsulated Bifidobacterium animalis sub sp lactis in yogurt and simulated gastric acidic condition - Sivakaran, M.; Ghoddusi, H. (University of Jaffna, 2018)
Probiotics are the cultures of live microorganisms which, when administered in adequate amounts confer a health benefit on the host. Fermented dairy products are considered as a suitable vehicle to carry probiotics where yogurt is the most common vehicle for incorporating probiotics. However the survival of probiotics can be affected by the food processing conditions as well as the low acidic environment of the gut. Encapsulation of probiotic bacteria can be considered as a suitable method to preserve the probiotics until they reach their site of action. The study was conducted in order to evaluate the effect of encapsulation on the survival of probiotic bacteria in acidic condition. Bifidobacterium animalis sub sp lactis (BB12) was encapsulated with sodium alginate and resistant starch and their survival was determined in yogurt as well as in simulated gastric condition. BB12 was mixed with 10 ml of 18g/L sodium alginate and 10 ml of 20g/L resistant starch and dropped in to sunflower oil in order to make encapsulated beads. Calcium chloride solution was used to harden the beads. pH change and titratable acidity of the yogurt added with encapsulated beads were measured. The number of encapsulated BB12 in yogurt declined by about 1 log10 CFU/ ml over the twelve days of storage, while the non-encapsulated bacterial viability declined by about 2 log10 CFU/ ml. The encapsulation of BB12 showed 1 log10 CFU/ ml decline over three hours of exposure to simulated gastric condition (pH 2.0, 3.0 and 4.0) where the non-encapsulated bacteria showed 2 log10 CFU/ ml decline for pH 3.0 or 4.0 at the same time 3 log10 CFU/ ml was observed for pH 2 treatment. A successful encapsulation was made using alginate and starch, but in overall the survival rate of encapsulated and free bacteria did not show any statistical difference
Keywords: BB12; Bifidobacterium; encapsulation; probiotics; yogurt